1998
DOI: 10.1016/s0014-5793(98)00367-6
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin is recovered in human plasma as conjugated derivatives which retain antioxidant properties

Abstract: Quercetin is one of the most abundant flavonoids in the human diet. This study aimed to determine the plasma concentrations of quercetin in 10 healthy volunteers after the consumption of a complex meal rich in plant products. Quercetin was determined in plasma (2 h before, and 3, 7 and 20 h after the meal), and in a duplicated portion of the meal by HPLC analysis with an electrochemical detection. The amount of ingested quercetin was estimated to be 87 mg. Before the meal, quercetin concentration in hydrolyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
319
3
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 516 publications
(335 citation statements)
references
References 24 publications
12
319
3
1
Order By: Relevance
“…This conclusion appears premature in the light of the fact that quercetin undergoes avid metabolism in species that may possess pharmacological activity, as hinted by our finding that isorhamnetin and tamarixetin are potent COX-2 inhibitors, at least in cells in vitro. Consistent with the notion that quercetin metabolites may be partially responsible for the pharmacological activity of the parent flavonol, quercetin conjugates have previously been found to retain, at least in part, the abilities of the parent molecule to exert antioxidation (Da Silva et al, 1998;Manach et al, 1998) and to inhibit xanthine oxidase and lipoxygenase (Day et al, 2000). Furthermore, products of the metabolic fission of quercetin have been shown to demonstrate greater antioxidant potency than their precursor (Merfort et al, 1996).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This conclusion appears premature in the light of the fact that quercetin undergoes avid metabolism in species that may possess pharmacological activity, as hinted by our finding that isorhamnetin and tamarixetin are potent COX-2 inhibitors, at least in cells in vitro. Consistent with the notion that quercetin metabolites may be partially responsible for the pharmacological activity of the parent flavonol, quercetin conjugates have previously been found to retain, at least in part, the abilities of the parent molecule to exert antioxidation (Da Silva et al, 1998;Manach et al, 1998) and to inhibit xanthine oxidase and lipoxygenase (Day et al, 2000). Furthermore, products of the metabolic fission of quercetin have been shown to demonstrate greater antioxidant potency than their precursor (Merfort et al, 1996).…”
Section: Discussionmentioning
confidence: 62%
“…A quercetin sulphate and two quercetin sulphate-glucuronides were also found in the perfused rat liver (Shali et al, 1991). Metabolites were also identified in human plasma following the ingestion of a complex meal rich in plant products (Manach et al, 1998, Day et al, 2001. Two pharmacokinetic studies of authentic quercetin in humans established that it is rapidly cleared from the organism (Gugler et al, 1975;Ferry et al, 1996).…”
mentioning
confidence: 99%
“…Thus, the own biological activity of the glucuronides should be considered, even though the possibility of hydrolysis into aglycones inside the cells is still under investigation (O'Leary et al, 2001;Shimoi et al, 2001). A few studies have reported antioxidative or anti-inflammatory activity of flavonoid conjugates (Manach et al, 1998;Hiermann et al, 1998;Day et al, 2000;Moon et al, 2001). The intestinal microflora, besides the deglycosylation of narirutin and hesperidin, has also the capacity to degrade the aglycones into phenolic acids such as p-hydroxyphenylpropionic, p-coumaric, and p-hydroxybenzoic acids (Booth et al, 1958;Scheline, 1991;Felgines et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…After ingestion of 80 -100 mg quercetin equivalents provided by onion, apple, or by a meal rich in fruits and vegetables, the plasma concentration of quercetin ranged from 0.30 to 0.74 mmol=l (Hollman et al, 1997;Manach et al, 1998). When flavanol monomers are supplied by green tea (90 -150 mg), by cocoa (70 -165 mg) or red wine (35 mg), their plasma concentrations reached 100 -700 nmol=l 250 -700 nmol=l, and 90 nmol=l, respectively (Lee et al, 1995;Unno et al, 1996;Yang et al, 1998;Richelle et al, 1999;Rein et al, 2000;Wang et al, 2000;Donovan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although all kinds of olive oils protect LDL from oxidation, virgin olive oil shows increased antioxidant activity because of its high phenolic content . Recent studies have shown the bioavailability of some phenols from wine or onions (Lapidot et al, 1998;Manach et al, 1998;Bell et al, 2000) but data on olive oil are scarce. Moreover, most of these studies have been done with rats or rabbits (Wiseman et al, 1996;Coni et al, 2000), but few with humans (Paganga & Rice-Evans, 1997;Miró -Casas et al, 2001).…”
Section: Introductionmentioning
confidence: 99%